IMPLEMENTATION OF THE MERDEKA CURRICULUM AT MTS LABORATORIUM JAMBI PROVINCE - Diana Rozelin; Hendri -; Mohd Arifullah (English Language, Linguistics, Literature, And Education Journal, 2025)
The merdeka curriculum at Mts Laboratirum Jambi has not been implemented optimally. This is because it was only implemented in the 2023/2024 school year. The purpose of this research is to find out how the implementation of the merdeka curriculum in learning activities carried out by English teachers. The view on the merdeka curriculum in this study used the opinion of Sugiono (2025). This research used qualitative descriptive methods, data collection in natural settings on primary data sources. Data collection techniques are carried out by observation, interviews and documentation. Data were processed using the Miles and Huberman method and analyzed using narrative. In collecting data about the implementation of the merdeka curriculum in learning activities carried out by the principal, deputy curriculum, and subject teachers. The results showed that: 1) based on the data obtained through observation of the application of the merdeka curriculum in learning activities carried out by English teachers, it shows that there are many activities carried out by English teachers in learning activities. These activities are carried out in stages. Data obtained through interviews regarding teacher difficulties in implementing the merdeka curriculum show that there are many difficulties and other related ones. The difficulties faced by teachers have problems including teachers have a lack of guidebooks to implement the merdeka Curriculum, students are lacking in the teaching and learning process, and students lack understanding of the material. 2) The socialization of curriculum implementation has not covered everything and is not optimal. Based on the data above, the researcher concludes that the implementation of the merdeka curriculum carried out by the principal, curriculum deputy, three English teachers at Jambi Laboratory MTS has not been maximized due to delays and implementation in the first year. The research is expected to provide input to local governments and stakeholders to be more vigorous and minimize gaps for schools that are new to implementing the merdeka curriculum.